2021
DOI: 10.1111/ajt.16163
|View full text |Cite
|
Sign up to set email alerts
|

Type 3 innate lymphoid cells are associated with a successful intestinal transplant

Abstract: Although innate lymphoid cells (ILCs) play fundamental roles in mucosal barrier functionality and tissue homeostasis, ILC‐related mechanisms underlying intestinal barrier function, homeostatic regulation, and graft rejection in intestinal transplantation (ITx) patients have yet to be thoroughly defined. We found protective type 3 NKp44+ILCs (ILC3s) to be significantly diminished in newly transplanted allografts, compared to allografts at 6 months, whereas proinflammatory type 1 NKp44−ILCs (ILC1s) were higher. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 47 publications
1
30
0
Order By: Relevance
“…Importantly, recent transplant studies have further strengthened the hypothesis that NKp44 + ILC3s are essential for maintaining homeostasis and protection of the GI tract: following human GI transplantation, recipients`ILCs quickly infiltrated into the GI graft (20) and moreover elevated frequencies of human NKp44 + ILC3s within the graft have been associated with successful intestinal transplants by reducing the risk of rejection (21). A similar observation has been made in leukemic patients after hematopoietic stem cell transplantation (HSCT).…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…Importantly, recent transplant studies have further strengthened the hypothesis that NKp44 + ILC3s are essential for maintaining homeostasis and protection of the GI tract: following human GI transplantation, recipients`ILCs quickly infiltrated into the GI graft (20) and moreover elevated frequencies of human NKp44 + ILC3s within the graft have been associated with successful intestinal transplants by reducing the risk of rejection (21). A similar observation has been made in leukemic patients after hematopoietic stem cell transplantation (HSCT).…”
Section: Introductionmentioning
confidence: 77%
“…Importantly, ILC3 generated on MSC produced high amounts of IL-22 with no co-secretion of IL-17A. This is an essential observation, as IL-17A was previously shown to exacerbate inflammation in IBD, whereas IL-22-secreting ILC3s have been described to be beneficial for IBD patients, leukemic patients after HSCT, and GI tract transplant recipients (15,21,25,27,(48)(49)(50). Several issues still have to be addressed concerning the role of ILC3 in inflammatory settings: an increase in IL-17A-producing ILC3s was reported in IBD, correlating with mucosal leakage in ulcerative colitis patients (27,51).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…There is currently no research directly connecting ILCs to MIRI, but there are some reports characterizing ILCs in ischemia-reperfusion injury to other organs. Kang et al (36) reported that ILC1s increased in high-fat diet mice following liver ischemia-reperfusion injury (IRI), with an increased production of IFN-g and TNF-a. Cao et al (37) reported that ILC2s could prevent renal injury in mice subjected to IRI, and that this effect was associated with M2 macrophage induction and ILC2 production of amphiregulin.…”
Section: The Role Of Ilcs In Myocardial Ischemia-reperfusion Injurymentioning
confidence: 99%
“…Kang et al. ( 36 ) reported that ILC1s increased in high-fat diet mice following liver ischemia-reperfusion injury (IRI), with an increased production of IFN-γ and TNF-α. Cao et al.…”
Section: The Role Of Ilcs In Myocardial Ischemia-reperfusion Injurymentioning
confidence: 99%